Enzymatic synthesis of geranyl acetate in batch and fed-batch reactors and evaluation of its larvicidal activity against Rhipicephalus (Boophilus) microplus. (September 2022) - Remonatto, Daniela; Fantatto, Rafaela Regina; Pietro, Rosemeire Cristina Linhari Rodrigues; Monti, Rubens; Oliveira, J. Vladimir; de Paula, Ariela Veloso; Bassan, Juliana Cristina
Abstract: Geraniol esters, such as geranyl acetate, are known to have antimicrobial and insect-repellent action, but their acaricidal activity has been little explored. This study aimed to investigate the solvent-free synthesis of geranyl acetate in batch (BSTR) and fed-batch (FBSTR) stirred tank reactors using the immobilized lipases NS 88011 and Novozym 435 and evaluate its larvicidal activity against the cattle tick Rhipicephalus ( Boophilus ) microplus . A central composite design (CCD) was used to maximize the synthesis of geranyl acetate in a BSTR. The independent variables were temperature reaction (40–60 °C), acetic acid/geraniol molar ratio (1:1–1:3), and enzyme loading (1–5% w/w in relation to the substrates). Novozym 435 yielded the best results, achieving 99% of geranyl acetate conversion using 1:3 acetic acid/geraniol molar ratio, 60 °C and 5% (w/w) of enzyme loading after 1 h of reaction in a BSTR. In the FBSTR system, a high content of geranyl acetate was obtained (about 80%) in 4 h of reaction using a 1:1 acetic acid/geraniol molar ratio, 60 °C and 5% (w/w) Novozym 435. Geranyl acetate showed potential as an acaricide, with an LC90 of 6.25 mg/mL and 100% mortality at a concentration of 12.5 mg/mL. Graphical Abstract: ga1 Highlights: Excess addition of geraniol was crucial to the shift of the esterification chemical-equilibrium. Novozym 435 yielded the best results, achieving 99% of geranyl acetate conversion. The excess of geraniol in the esterification was benefic for the lipase operational stability. Fed-batch system allowed for greater use of geraniol, providing economic and productive benefits. Geranyl acetate was revealed to be a potential acaricide.